2018
DOI: 10.1021/acs.joc.7b03109
|View full text |Cite
|
Sign up to set email alerts
|

Intra- versus Intermolecular Carbon-to-Carbon Proton Transfers in the Reactions of Arynes with Nitrogen Nucleophiles: A DFT Study

Abstract: Carbon-to-carbon proton transfer (PT) is an elementary reaction in organic chemistry. Herein we report a systematic DFT study on the carbon-to-carbon proton transfers in the reactions of arynes with nitrogen nucleophiles, including tertiary amines, aziridines, imines, and N-heteroarenes. DFT calculations indicated that the Gibbs energies of activation for the 1,4- and 1,5-proton transfers involved are lower than 20 kcal/mol in most cases. We also found that the Bell-Evans-Polanyi principle applies to the 1,4-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…Using the optimized conditions, a collection of substituted arynes and imides was reacted. According to the proposed mechanism, the aryne insertion proceeds via intermediacy of 8 . ,, Greaney et al showed that a major byproduct results from premature protonation of 8 . Remarkably, under flow conditions, even the use of wet acetonitrile did not increase the amount of byproduct, thus rendering the flow process more sustainable.…”
supporting
confidence: 93%
“…Using the optimized conditions, a collection of substituted arynes and imides was reacted. According to the proposed mechanism, the aryne insertion proceeds via intermediacy of 8 . ,, Greaney et al showed that a major byproduct results from premature protonation of 8 . Remarkably, under flow conditions, even the use of wet acetonitrile did not increase the amount of byproduct, thus rendering the flow process more sustainable.…”
supporting
confidence: 93%
“…The formation of epoxides 9 , 14 , and 16 includes sequential 1,2‐elimination, 1,2‐nucleophilic addition, 1,4‐proton shift, [16] and the Johnson‐Corey‐Chaykovsky [17,18] reaction (i. e., three‐membered ring formation followed by α‐elimination) shown in Scheme 3. Reactions involving arynes as the intermediates are sensitive to the media, such as chloroform and acetonitrile [19] . The protons therein might offer a chance of intermolecular transfer to the betaine intermediates like 11 through the pathway “b”.…”
Section: Resultsmentioning
confidence: 99%
“…Reactions involving arynes as the intermediates are sensitive to the media, such as chloroform and acetonitrile. [19] The protons therein might offer a chance of intermolecular transfer to the betaine intermediates like 11 through the pathway "b". This possible interference, however, was overwhelmed by the intramolecular 1,4-proton shift pathway "a", which led betaines 11 to sulfonium ylides 12.…”
Section: Preparation Of Epoxides Through a Domino Process Including 1mentioning
confidence: 99%
“…During our recent exploration of the chemistry of imines activated by arynes, we unexpectedly found that a three-component mixture of imine 1a , 2-(trimethylsilyl)­phenyl triflate ( 2a ) (as a benzyne precursor), and carbon tetrachloride ( 3a ) in the presence of CsF proceeded in acetonitrile at 65 °C to afford polychlorinated compound 4a in 87% yield (Table , entry 1). This three-component reaction involves an unprecedented formal insertion of an imine and an aryne into the C–Cl bond of carbon tetrachloride.…”
mentioning
confidence: 99%
“…In addition to the reaction pathway mentioned above, there are two competing pathways for aryl anion A (Figure b). One is the intramolecular 1,4-proton transfer via transition state TS3 (the Gibbs energy of activation is 20.8 kcal/mol). , The other is the intermolecular proton abstraction from MeCN via transition state TS4 (the Gibbs energy of activation is 13.0 kcal/mol). , In comparison to the chlorine transfer, these two proton transfer processes are both kinetically disfavored . To verify whether the same conclusions hold for nitrogen heteroarenes, we performed additional DFT calculations by using isoquinoline as a representative example of nitrogen heteroarenes (Figure c).…”
mentioning
confidence: 99%